An in-depth analysis of ethics teaching in Canadian physiotherapy and occupational therapy programs. (20th November 2015) - Laliberté, Maude; Hudon, Anne; Mazer, Barbara; Hunt, Matthew R.; Ehrmann Feldman, Debbie; Williams-Jones, Bryn
Abstract: Purpose : The purpose of this study was to examine current approaches and challenges to teaching ethics in entry-level Canadian physiotherapy (PT) and occupational therapy (OT) programs. Methods : Educators responsible for teaching ethics in the 28 Canadian PT and OT programs ( n  = 55) completed an online survey. Results : The quantity of ethics teaching is highly variable, ranging from 5 to 65 h. Diverse obstacles to ethics teaching were reported, relating to the organization and structure of academic programs, student issues and the topic of ethics itself. Specific challenges included time constraints, large class sizes, a lack of pedagogical tools adapted to teaching this complex subject, a perceived lack of student interest for the subject and a preference for topics related to clinical skills. Of note, 65% of ethics educators who participated in the survey did not have any specialized training in ethics. Conclusion : Significant cross-program variation in the number of hours dedicated to ethics and the diversity of pedagogical methods used suggests that there is little consensus about how best to teach ethics. Further research on ethics pedagogy in PT and OT programs (i.e. teaching and evaluation approaches and effectiveness of current ethics teaching) would support the implementation of more evidence-based ethics education. Implications for Rehabilitation: Ethics educators in Canadian PT and OT programs are experimenting with diverse educational approaches to teach ethical reasoning and decision-making to students, including lectures, problem-based learning, directed readings, videos, conceptual maps and clinical elective debriefing, but no particular method has been shown to be more effective for developing ethical decision-making/reasoning. Thus, research on the effectiveness of current methods is needed to support ethics educators and programs to implement evidence-based ethics education training. In our survey, 65% of ethics educators did not have any specialized training in ethics. Ensuring that educators are well equipped to support the development of necessary theoretical and applied competencies can be promoted by initiatives including the creation of tailored ethics teaching and evaluation tools, and by establishing communities of practice among ethics educators. This survey identified heterogeneity in ethics teaching content, format and duration, and location within the curriculum. In order to be able to assess more precisely the place accorded to ethics teaching in PT and OT programs, careful mapping of ethics content inside and across rehabilitation programs is needed – both in Canada and internationally. These initiatives would help advance understanding of ethics teaching practices in rehabilitation.